Halal Certification Assistance for Micro and Small Enterprises Producing Traditional Medicine Products through Participatory Work Lectures: Pendampingan Sertifikasi Halal Bagi UMK Produk Obat Tradisional Melalui Kuliah Kerja Partisipatif - Laily Isnawati; Nurul Hidayah; Reza Yazidurrahman; Muhammad Rizal Fahmi; Binti Khusnul Khotimah; Satria Sholeh Trisnanto; Tina Astuti; Abdullah Huzaepi; Aena Sulastri; Ronawan Anshori; Aulia Kurnia; Putri Aldina Fahira; Ihsaniati Rohmani; Andre Pratama Saputra; Annisa Annisa; Nurfitrah Ramdhani; Humaidi Humaidi; Ainun Sifak; Nova Motmainnah (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
The halal certification assistance program for Micro and Small Enterprises (MSEs) producing traditional medicine aims to enhance entrepreneurs’ understanding of the importance of halal product assurance. This initiative was carried out by the Participatory Work Lecture (KKP) team of the State Islamic University of Mataram using the Asset-Based Community Development (ABCD) approach. The program focused on MSEs in Peresak Village that produce traditional herbal medicines made from local plants, particularly Tegining Teganang (Cassia Planisiliqua). This plant is known for its medicinal benefits, such as treating burns, skin itching, sprains, and venomous bites. The assistance included several stages, starting with halal certification socialization, verification of ingredients and production processes, and technical guidance for submitting halal certification applications. The results indicate that entrepreneurs gained greater awareness of halal certification requirements and its positive impact on product value and consumer trust. Furthermore, the program contributed to improving the competitiveness of traditional herbal products in the halal market and encouraged MSEs to manage their products more professionally.